A Segmentation of Mall Shopping Motivations in the South African Gauteng Provincial Context - Jogee, R; Callaghan, CW (My University, 2014)
Consumer markets, globally, exhibit increasing diversity. Shopping malls that do not take cognisance of this diversity, along all appropriate dimensions, can lose market share to competitors that do. Despite extensive literature that is based on research done in other countries, absent from the South African literature is a current typology of market segmentation of mall consumers by mall shopping motivations. Using a sample of 224 mall consumers drawn from Gauteng, the economic hub of the country, k-means segmentation was used to test theory that relates different characteristics of consumers and their mall choices. On the basis of this analysis, a typology of shopping mall consumers is developed according to their preferences, or motivations, for mall shopping. Six different segments were found to be associated with different mall shopping preferences and other characteristics. These segments were classified as ‘Low Engagement Shoppers’; ‘Mean Oriented Shoppers’; ‘Brand Oriented Shoppers’; ‘Utilitarian Oriented Shoppers’ and ‘Ascetic Oriented Shoppers’. It is argued that knowledge of such typologies may be important in the South African context due to the increasing societal diversity that malls need to be able to take advantage of in an increasingly competitive environment.
Keywords: Trends in mall shopping; Shopper preferences; K-means clustering